Comparison of contrast‐enhanced ultrasonography with virtual touch tissue quantification in the evaluation of focal liver lesions. Issue 6 (18th February 2016) - Wu, Jing‐ping; Shu, Rui; Zhao, Yu‐zhen; Ma, Guo‐lin; Xue, Wei; He, Qi‐jia; Hao, Mei‐na; Liu, Yawu
ABSTRACT: Purpose: To evaluate the diagnostic efficacy of virtual touch tissue quantification (VTQ) and contrast‐enhanced ultrasonography (CEUS), separately and in combination, in diagnosing malignant focal liver lesions (FLLs). Methods: Forty‐six patients with 55 FLLs (28 benign and 27 malignant) underwent both VTQ and CEUS. The diagnostic values of VTQ and CEUS, alone and in combination, were compared. Results: The diagnostic sensitivity, specificity, accuracy, positive predictive value (PPV), and negative predictive value (NPV) of CEUS were 92.6% (25/27), 96.4% (27/28), 94.5% (52/55), 96.2% (25/26), and 93.1% (27/29), respectively. The diagnostic sensitivity, specificity, accuracy, PPV, and NPV of VTQ with a cutoff of 2.22 m/s were 51.9% (14/27), 85.7% (24/28), 69.1% (38/55), 77.8% (14/18), and 64.9% (24/37), respectively. The diagnostic sensitivity, specificity, accuracy, PPV, and NPV of VTQ and CEUS combined were 96.3% (26/27), 82.1% (23/28), 89.1% (49/55), 83.9% (26/31), and 95.8% (23/24), respectively. Comparing the accuracies of the three methods, the diagnostic values of CEUS and of the combination of CEUS with VTQ were significantly higher than those of VTQ alone ( p ≤ 0.01). There was no significant difference between the combination of CEUS with VTQ and CEUS ( p = 0.49). Conclusions: CEUS is superior to VTQ in diagnosing malignant FLLs. Adding VTQ to CEUS did not improve the diagnosis of FLLs. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 44 :347–353, 2016